A Novel Strategy for Efficient Agaro-Oligosaccharide Production Based on the Enzymatic Degradation of Crude Agarose in Flammeovirga pacifica WPAGA1 - Gao, Boliang; Li, Li; Wu, Hui; Zhu, Du; Jin, Min; Qu, Wu; Zeng, Runying (Frontiers in Microbiology, 2019)
To avoid conflict between biofuel and food resource production, marine macroalgae (main algal polysaccharides) have been suggested as potent feedstock for biofuel production. Flammeovirga pacifica WPAGA1, a typical marine polysaccharide-degrading bacterium, can utilize crude agarose as the sole carbon source. Transcriptomic analysis was performed to further investigate the metabolic pathway of environmental-friendly utilization of crude agarose in F. pacifica WPAGA1. All of these enzymes were overexpressed in Escherichia coli BL21 (DE3), and the purified enzymes were characterized in vitro. As a result, the pathway of crude agarose which desulfurized and hydrolyzed by enzymes to produce fermentable sugar is clear. Interestingly, sole neoagarobiose (~450 mg/L) was produced from crude agarose as a feedstock using engineered E. coli BL21(DE3). This study firstly reveals the metabolic pathway of crude agarose in strain WPAGA1 and establishes a novel and environmental-friendly strategy for neoagarobiose production using crude agarose as cost-effective and non-food based feedstock.